Fabry–Pérot cavity smart windows with superior solar and thermal modulation capabilities - Jin Li; Chunhui Zhang; Yunxiang Chen; Ke Jiao; Zhang Chen; Yifei Liu; Yanfeng Gao; Zongtao Zhang (Journal of Materiomics)
Smart windows are an important strategy to reduce the energy consumption in buildings, which accounts for as much as 30%–40% of the society's energy consumption. VO2-based thermochromic materials can intelligently regulate the solar heat gains of building interiors. However, the unmatched thermal emissivity (ɛ) modulation of traditional VO2/glass systems, i.e., high emissivity at low temperatures and low emissivity at high temperatures, leads to additional heating and cooling energy loads in winter and summer, respectively. In this study, we propose a novel VO2/polyacrylonitrile (PAN)/AgNW multilayer possessing flexible Ag nanowire supported Fabry–Pérot cavities, which synchronously achieves high modulation abilities in both solar spectrum (ΔTsol of 13.6%) and middle infrared region (Δɛ of 0.50 at 8–13 μm). These achievements are the best among reports for pure VO2 smart windows. This study provides a flexible and effective protocol to dynamically enhance the light and heat utilization for practical building windows.